Teacher Professionalism and Learning Environment in Enhancing Student Motivation: An SDG 2030 Perspective - Inayati, Nurul Latifatul; Febriandika , Nur Rizqi; Dartim; Mustofa, Triono Ali; Ihsan, Muhammad Zidan Nur; Silvani Yuzarni (Universitas Muhammadiyah Surakarta, 2025)
Objective: This study aims to analyze the influence of teacher professionalism, school environment, and student stress level on learning motivation. This study tested the direct relationship between variables in one integrated structural model. The focus of the research is on the context of pesantren education in Indonesia. Theoretical framework: Based on the theory of learning motivation, the concept of teacher professionalism, and the theory of the learning environment as determinants of learning quality. The conceptual model places professionalism and the school environment as the main predictors of student motivation. Literature review: Previous studies have discussed the relationship between the school environment and teacher professionalism, as well as stress and motivation to learn separately. However, the integration of the three variables in a single SEM model in Indonesia is still limited. Methods: A quantitative approach is used with Structural Equation Modeling (SEM) analysis. The sample consisted of 201 students of the Baitur Rohmah Islamic Boarding School Muhammadiyah. Results: Teacher professionalism has a significant and dominant effect on learning motivation (β = 0.360). The school environment also had a positive effect (β = 0.202). Teachers play an important role in shaping a conducive learning environment. Implications: Strengthening teacher professionalism is a key strategy to increase motivation and the quality of education. Collaboration with the government and relevant institutions supports the achievement of quality education (SDGs 4). Novelty: The novelty of the research lies in the integration of teacher professionalism, the school environment, and student stress in one structural model. This study enriches the empirical literature in the context of pesantren education in Indonesia.